2007
DOI: 10.1016/j.neuroscience.2007.09.069
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of netrin-1 receptors by amphetamine in the adult brain

Abstract: Netrin-1 is a guidance cue molecule fundamental to the organization of neuronal connectivity during development. Netrin-1 and its receptors, deleted in colorectal cancer (DCC) and UNC-5 homologues (UNC-5), continue to be expressed in the adult brain, although neither their function nor the kinds of events that activate their expression are known. Two lines of evidence suggest a role for netrin-1 in amphetamine-induced dopamine plasticity in the adult. First, DCC is highly expressed by adult dopamine neurons. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 63 publications
10
43
1
Order By: Relevance
“…There were no differences in the volume of TH-positive fibers between saline-and AMPH-treated littermates in any of the mPFC subregions analyzed (Figure 2c These data indicate that the same AMPH regimen that induces profound changes in adult mPFC DA synaptic connectivity when administered during early adolescence does not alter dopamine connectivity within this region when administered during adulthood (Figure 2d). We have previously shown, that in contrast to early adolescence (Yetnikoff et al, 2011), exposure to the exact same regimen of amphetamine upregulates DCC expression in the VTA when given to adult mice and rats (Yetnikoff et al, 2007(Yetnikoff et al, , 2010. This age-dependent effect is consistent with the idea that DCC signaling within dopamine neurons mediates different events at different developmental times (Flores, 2011).…”
Section: Amph In Adolescence But Not In Adulthood Alters Dopamine Isupporting
confidence: 82%
See 1 more Smart Citation
“…There were no differences in the volume of TH-positive fibers between saline-and AMPH-treated littermates in any of the mPFC subregions analyzed (Figure 2c These data indicate that the same AMPH regimen that induces profound changes in adult mPFC DA synaptic connectivity when administered during early adolescence does not alter dopamine connectivity within this region when administered during adulthood (Figure 2d). We have previously shown, that in contrast to early adolescence (Yetnikoff et al, 2011), exposure to the exact same regimen of amphetamine upregulates DCC expression in the VTA when given to adult mice and rats (Yetnikoff et al, 2007(Yetnikoff et al, , 2010. This age-dependent effect is consistent with the idea that DCC signaling within dopamine neurons mediates different events at different developmental times (Flores, 2011).…”
Section: Amph In Adolescence But Not In Adulthood Alters Dopamine Isupporting
confidence: 82%
“…DCC expression in dopamine neurons is high during early development and adolescence, in line with the maturational timeline of dopamine pathways. Interestingly, DCC expression is substantially lower during adulthood, suggesting that DCC signaling may play a different, more local, role in the adult brain (Osborne et al, 2005;Grant et al, 2007;Manitt et al, 2010;Reyes et al, 2013;Yetnikoff et al, 2007Yetnikoff et al, , 2010Yetnikoff et al, , 2011Yetnikoff et al, , 2013a. Using rodents, we showed that DCC signaling within the ventral tegmental area (VTA) dopamine neurons determines the extent of their innervation to the mPFC specifically during adolescence and, in turn, organizes the structure and function of mPFC local circuitries (Manitt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The cellular and molecular processes mediating these effects are essentially unknown. Our past work identified a role for the netrin-1 receptor DCC (deleted in colorectal cancer) in the functional organization of mesocorticolimbic DA systems (Flores et al, 2005Grant et al, 2007Grant et al, , 2009Yetnikoff et al, 2007Yetnikoff et al, , 2010, leading us to propose that DCC-mediated netrin-1 signaling is a mechanism whereby risk factors exert their enduring effects on DA function (Flores, 2011). Here, we report that DCC contributes to the organization of mesocorticolimbic DA systems by influencing medial prefrontal cortex (mPFC) DA synaptic connectivity.…”
Section: Introductionmentioning
confidence: 73%
“…Finally, amphetamine-induced sensitization and upregulation of VTA DCC are prevented by cotreatment of an N-methyl-D-aspartate antagonist during the pretreatment phase. 82,86 These findings suggest that the upregulation of VTA DCC expression by repeated amphetamine exposure may be implicated in the development of sensitization.…”
Section: Upregulation Of DCC Expression In the Vta By Amphetamine Expmentioning
confidence: 84%
“…Deleted in colorectal cancer continues to be expressed in tyrosine hydroxylase-positive neurons during peripubertal (postnatal day 33 ± 2 in mice; postnatal day 33 in rats) and adult periods, consistent with previous reports. [81][82][83] Remarkably, there is a dramatic emergence of UNC5H expression by DA neurons in the peripubertal period, which persists until adulthood. 48,82,83 Importantly, from the peripubertal period onward, single VTA DA neurons coexpressed both UNC5H and DCC receptors (Fig.…”
Section: Expression Of Netrin-1 DCC and Unc5h By Da Neurons: Peripubmentioning
confidence: 99%